Creating the Leyndell RPG Game Using the Godot Engine - Ira Windarti; Sari Noorlima Yanti (Lentera Ilmu Nusantara, 2026)
This research aims to design and build Leyndell-RPG games along with web-based game distribution websites that are able to support the process of digital game information, transactions, and distribution. The development method used is Waterfall which includes the stages of needs analysis, design, implementation, testing, and maintenance. Games are developed using the Godot Engine, while distribution websites are built with Next.js, TypeScript, and MySQL databases. System testing is carried out using the black box testing method on user, admin, and browser compatibility. The test results show that all the main features of the user and admin systems run according to the needs designed, and the website is well accessible on the Google Chrome and Microsoft Edge browsers. Thus, the Leyndell–RPG game distribution website was declared successful and was able to provide effective support for users and developers in the digital game distribution process.